Water Lithography: "Print‐to‐pattern": Silk‐Based Water Lithography (Small 47/2018). Issue 47 (26th November 2018) - Liu, Zhen; Zhou, Zhitao; Zhang, Shaoqing; Sun, Long; Shi, Zhifeng; Mao, Ying; Liu, Keyin; Tao, Tiger H.
Abstract : In article number 1802953, Tiger H. Tao and co‐workers report a silk‐based water lithography technique. This work introduces a wafer‐scale, all‐water‐based, chemical‐free, biopatterning method that allows for rapid prototyping of biologically functional devices and interfaces in an extremely fast fashion, and importantly, in ambient conditions, on both planar and curved surfaces.